Synchrotron microbeam radiotherapy evokes a different early tumor immunomodulatory response to conventional radiotherapy in EMT6.5 mammary tumors. (April 2019) - Yang, Yuqing; Swierczak, Agnieszka; Ibahim, Mohammad; Paiva, Premila; Cann, Leonie; Stevenson, Andrew W.; Crosbie, Jeffrey C.; Anderson, Robin L.; Rogers, Peter A.W.
Highlights: Conventional radiotherapy and synchrotron microbeam radiotherapy elicit different tumor immune responses. Conventional but not microbeam radiotherapy induces infiltration of macrophages and neutrophils into mammary tumors. In contrast, higher numbers of T cells and pro-inflammatory genes concentrate in tumors following microbeam radiation compared to conventional radiation. Abstract: Background: Synchrotron microbeam radiation therapy (MRT) is a new, evolving form of radiotherapy that has potential for clinical application. Several studies have shown in preclinical models that synchrotron MRT achieves equivalent tumor control to conventional radiotherapy (CRT) but with significantly reduced normal tissue damage. Methods: To explore differences between these two modalities, we assessed the immune cell infiltrate into EMT6.5 mammary tumors after CRT and MRT. Results: CRT induced marked increases in tumor-associated macrophages and neutrophils while there were no increases in these populations following MRT. In contrast, there were higher numbers of T cells in the MRT treated tumors. There were also increased levels of CCL2 by immunohistochemistry in tumors subjected to CRT, but not to MRT. Conversely, we found that MRT induced higher levels of pro-inflammatory genes in tumors than CRT. Conclusion: Our data are the first to demonstrate substantial differences in macrophage, neutrophil and T cell numbers in tumors following MRT versus CRT, providing support for the concept that MRT evokes a different immunomodulatory response in tumors compared to CRT.